2010
DOI: 10.1155/2010/439230
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antiphosphatidyl‐Serine Antibody and Antiphosphatidyl‐Inositol Antibody in Ischemic Stroke Patients

Abstract: Antiphospholipid syndrome is characterized by arterial or venous thrombosis and the presence of antiphospholipid antibodies (aPL). We measured β2-GPI aCL, IgGaCL, LA, antiphosphatidyl-serine antibody (PS), and antiphosphatidyl-inositol antibody (PI) in each patient at one month after the onset of stroke. In addition, carotid artery echography was performed in patients positive for PI or PS. Among the 250 patients, 13.6% (34/250) were positive for either PI or PS, and 6.8% (17/250) were positive for both. Carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Moreover, recent data support an association between aPS and pathogenesis of thrombosis. 8,18,27 Thrombosis and recurrent pregnancy loss are the main clinical presentations in the Sapporo criteria. Our results showed that 47.6% and 52% of patients with thrombosis and recurrent pregnancy failure, respectively, had a positive result for aPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent data support an association between aPS and pathogenesis of thrombosis. 8,18,27 Thrombosis and recurrent pregnancy loss are the main clinical presentations in the Sapporo criteria. Our results showed that 47.6% and 52% of patients with thrombosis and recurrent pregnancy failure, respectively, had a positive result for aPS.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] The clinical significance of other autoantibodies, including those directed against prothrombin, annexin, phosphatidylinositol and phosphatidylserine (PS), is still undetermined. 4,18,19 Recent studies suggested some association between these autoantibodies and the clinical features of APS. 3,20 Adler et al 21,22 found that autoantibodies against PS could interfere with the normal formation of syncytiotrophoblast, thus affecting placental development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 70.6% of these patients were positive for antinuclear antibodies. The authors pointed out that aPL are a risk factor for cerebral infarction especially in SLE patients and in younger population (Okuma et al, 2010). Moreover, a significant association between CIMT and the risk of ischemic stroke has been well documented (Chambless et al, 2000;Touboul et al, 2005).…”
Section: Selected Non-criteria Antiphospholipid Antibodies and Their mentioning
confidence: 99%
“…Antiphospholipid syndrome (APS) is an acquired autoimmune disorder that results in a hypercoagulable state characterized by recurrent venous and/or arterial thrombosis [ 1 ]. Antiphospholipid antibodies are directed against proteins that bind to anionic phospholipids on plasma membranes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%